Imum Gampong Authority as Amil of Zakat According to Fiqh and Qanun of Aceh - Safriadi Safriadi; Muhammad Diah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Imum Gampong has a share and role in amil of zakat. The research aims to determine the position of the Imum Gampong in amil of zakat as seen from the perspective of fiqh and qanun of Aceh. This research uses a descriptive analysis method with a qualitative approach. The results of this research indicate that in zakat management, according to fiqh, the Imum Gampong has the authority to determine, establish, and inaugurate zakat administrators (amil of zakat) at the village (gampong) level. In contrast, according to the qanun of Aceh, besides being given the authority to inaugurate the zakat administrator of the gampong (amil of zakat) at the village level, imum gampong can also act as amil of zakat itself so that the imum gampong is also entitled to ujrah (fees) of the asnaf of amil of zakat in addition to the salary from the government for the occupation. In fact, in Acehnese society, the imum gampong is part of the amil zakat, takes costs from the amil zakat part, and is entitled to fees of the asnaf of amil of zakat. Based on the two sources of law on the authority of the Imum Gampong, the position of the Imum Gampong in the fiqh perspective is narrower than the perspective of the Qanun of Aceh. According to the Qanun of Aceh, the Imum Gampong has four tasks in zakat management: appointing administrators, recording, collecting, and distributing zakat to zakat mustahiq. Recommend stakeholders to revise the provisions in the Aceh qanun to be adapted to the fiqh concept that is developing in Aceh province.